"You're O.K. Anesthesia": Closed Reduction of Displaced Pediatric Forearm and Wrist Fractures in the Office Without Anesthesia. Issue 10 (22nd November 2022) - Livingstone, John; Opanova, Maria; Beaman, Amanda; Radi, Joshua; Izuka, Byron
Abstract : Background: Angulated wrist and forearm fractures are among the most common pediatric fractures, and they often require closed reduction with anesthesia. There are several issues associated with pediatric anesthesia including the low but non-zero risk of significant complications, increased physician and staff time and effort, and increased cost. Despite these issues, there have not been any studies to prove that using anesthesia results in better outcomes or higher caregiver satisfaction in comparison to performing closed reductions without anesthesia. The purpose of this study was to evaluate the quality of closed reductions of angulated pediatric wrist and forearm fractures and to determine caregiver satisfaction with an anesthesia-free reduction technique. Methods: This study included 54 pediatric patients with closed, angulated fractures of the radius or combined radial and ulnar shafts. All closed reductions were performed by a single pediatric fellowship-trained orthopaedic surgeon in the office setting without any anesthesia. Radiographs were obtained to assess the quality of the reduction. At the first follow-up visit, caregivers were asked about their interim use of pain medications. Caregivers were later surveyed about patient use of analgesics and their satisfaction with an anesthesia-free reduction technique. Results: The average age of the 54 patients in this study was 9 years (1.8 to 16.8 y). Thirty-three fractures were combined radial and ulnar forearm shaft fractures, 18 were distal radius fractures, and 3 were radial shaft fractures. ≤10 degrees of residual angulation was achieved in 98% of patients. Nine percent (5/54) of the patients used ibuprofen or acetaminophen for pain control. Seventy eight percent (42/54) of the caregivers responded to the telephone and email surveys. All responding caregivers stated that the patients returned to full function and had satisfactory outcomes. Ninety eight percent (41/42) of the caregivers stated they would choose the same anesthesia-free reduction technique again. Conclusions: Closed reduction of angulated pediatric wrist and forearm fractures in the office without anesthesia can achieve satisfactory reductions and high caregiver satisfaction while eliminating the risks and complications associated with pediatric anesthesia. Level of Evidence: Level IV Case series.